Appendicular Skeletal Muscle Index and HbA1c Evaluate Liver Steatosis in Patients With Metabolic Associated Fatty Liver Disease - Jin, Rui; Wang, Xiaoxiao; Li, Xiaohe; Yang, Jia; Liu, Baiyi; Wei, Lai; Liu, Feng; Rao, Huiying (Frontiers in Medicine, 2022)
Background and Aim(s): Liver steatosis, as the main feature of metabolic associated fatty liver disease (MAFLD), was associated with the progression of liver fibrosis and metabolic syndrome, which needed to be estimated accurately. In this study, we explored the significance of appendicular skeletal muscle index (ASMI) in evaluating liver steatosis of MAFLD patients. Methods: 899 cases with MAFLD from 2017-2018 National Health and Nutrition Examination Surveys (NHANES) database were included. All the analyzed data were obtained from NHANES database. The association between ASMI and liver steatosis were evaluated using R and EmpowerStats. Results: MAFLD individuals were randomly divided into a training (n=450) and validation cohort (n=449). In univariate analysis, HbA1c, arms fat, arms lean mass, legs lean mass, trunk lean mass, total fat, total lean mass and ASMI were significantly associated with liver steatosis (p < 0.05). Multivariate analysis showed that HbA1c (OR: 1.6732; 95% CI: 1.2753 - 2.1929, p = 0.0002) and ASMI (OR: 1.6723; 95% CI: 1.1760 - 2.5204, p = 0.0052) were independently associated with severe liver steatosis. ASMI accurately evaluated severe liver steatosis with an AUROC of 0.73 and 0.81 in training and validation cohort, respectively. Compared with ASMI only, ASMI combined with HbA1c improved the AUROC to 0.85 and 0.88. Furthermore, the AUROC of our model was superior to FLI in the evaluation of liver steatosis. Conclusions: ASMI combined with HbA1c has good evaluation value for liver steatosis in MAFLD patients, which might be beneficial for the management of MAFLD clinically.